High-Throughput AFLP Analysis Using Infrared Dye-Labeled Primers and an Automated DNA Sequencer. (February 2001) - Myburg, A.A.; Remington, D.L.; O'Malley, D.M.; Sederoff, R.R.; Whetten, R.W.
Amplified fragment length polymorphism (AFLP) analysis is currently the most powerful and efficient technique for the generation of large numbers of anonymous DNA markers in plant and animal genomes. We have developed a protocol for high-throughput AFLP analysis that allows up to 70 000 polymorphic marker genotype determinations per week on a single automated DNA sequencer. This throughput is based on multiplexed PCR amplification of AFLP fragments using two different infrared dyelabeled primer combinations. The multiplexed AFLPs are resolved on a two-dye, model 4200 LI-COR ® automated DNA sequencer, and the digital images are scored using semi-automated scoring software specifically designed for complex AFLP banding patterns (AFLP-Quantar™). Throughput is enhanced by using high-quality genomic DNA templates obtained by a 96-well DNA isolation procedure.